Can preclinical drug development help to predict adverse events in clinical trials?. Issue 1 (January 2022) - Chi, Lap Hing; Burrows, Allan D.; Anderson, Robin L.
Highlights: Adverse events are a major cause of attrition during therapeutic development. Serious adverse events have caused organ failure, cancer onset and even death. Conventional safety testing tools may not faithfully represent human physiology. Novel in vitro, ex vivo and in vivo models that have revealed toxicity mechanisms have been developed and should be adopted for safety testing. Abstract: The development of novel therapeutics is associated with high rates of attrition, with unexpected adverse events being a major cause of failure. Serious adverse events have led to organ failure, cancer development and deaths that were not expected outcomes in clinical trials. These life-threatening events were not identified during therapeutic development due to the lack of preclinical safety tests that faithfully represented human physiology. We highlight the successful application of several novel technologies, including high-throughput screening, organs-on-chips, microbiome-containing drug-testing platforms and humanised mouse models, for mechanistic studies and prediction of toxicity. We propose the incorporation of similar preclinical tests into future drug development to reduce the likelihood of hazardous therapeutics entering later-stage clinical trials.